Perbedaan Problem Solving dengan PBL Menggunakan Website HTML5 dan Ispring pada Materi Dinamika Gerak - MT. Ester; PS. Mariati (Mataram University, 2026)
The low level of students' problem-solving skills in the topic of motion dynamics indicates the need for learning media that can effectively support students in analyzing and solving physics-related problems. This study aimed to analyze the differences in students' problem-solving abilities through the implementation of HTML5 website-based media and iSpring media using the Problem-Based Learning (PBL) model on motion dynamics material. This research employed a quasi-experimental method with a pretest-posttest control group design involving two experimental classes. Data were analyzed using normality tests, homogeneity tests, independent sample t-tests, and N-gain tests. The results showed that the average posttest score of students' problem-solving abilities in the class using HTML5 website-based media was 78.93, which was higher than that of the class using iSpring media at 71.86. A significance value of 0.016 indicated a significant difference in problem-solving abilities between the two classes, while the N-gain scores of 0.64 and 0.50 demonstrated moderate improvement in both groups. The study concludes that the use of HTML5 website-based media through the PBL model is more effective than iSpring media in enhancing students' problem-solving abilities in motion dynamics material.